Rice stem lodging properties and bending modeling under the influence of circadian temperature difference - Wang, Bangzhui; Tang, Zhong; Lao, Liyun; Wang, Guoqiang; Jing, Tiantian; Yu, Yao (International Journal of Agricultural and Biological Engineering, 2024)
Under diurnal temperature stress, the vascular bundle content of mature rice stems will change which will cause a change in the modulus of elasticity. Therefore, the rice stems will collapse with the reduction in bending resistance because of the change in the modulus of elasticity. In order to reveal the distribution of vascular bundle gradients in rice stems under different climatic temperatures and explore the locations where stems are prone to bending and the form of stem damage, this study established a model of stem stiffness under free loading based on observing microstructure of the rice. The lodging characteristics of rice stems was explored seldom in different environmental temperatures from a micro structure of rice stems. So, the statistical analysis and t-tests were carried out on stems 1 to 4 in combination for cantilever bending tests at room temperature on stem internodes 3, versus three-point bending tests at –10°C to 65°C temperature treatment. Results showed that the bending resistance of the stem can be well predicted by using the vascular bundle distribution regression model and the variable stiffness mechanical model. The bending resistance of No. 3 stem was established by using the results obtained from the three-point bending test in a temperature range between 10°C-65°C. The correction coefficient TF of stem bending resistance under temperature difference induced stress was established based on the Gauss regression model. Statistical analysis showed that the bending resistance of No.3 stem was relatively large in a temperature range of 16°C-34°C. This study elucidated the variations of the mechanical properties of rice stems under temperature difference induced stress and provided a theoretical foundation for understanding the lodging characteristics of rice during mechanized harvesting. Keywords: rice stem, vascular gradient, stiffness model, stem bending, temperature stress DOI: 10.25165/j.ijabe.20241703.8585 Citation: Wang B Z, Tang Z, Lao L Y, Wang G Q, Jiang T T, Yu Y. Rice stem lodging properties and bending modeling under the influence of circadian temperature difference. Int J Agric & Biol Eng, 2024; 17(3): 21-32.